Isolasi dan Karakterisasi Bakteri Pemacu Pertumbuhan Tanaman (Plant Growth Promoting Rhizobacteria) Asal Tanah Desa Akar-Akar, Lombok Utara - Shania Corolla Azzahra; Yunus Effendy; Sudono Slamet (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
Plant Root Growth Promoting Bacteria or PGPR are bacteria that colonize plant rooting areas or the rhizosphere to increase the quality or quantity of plant growth. PGPR can provide dissolved phosphate for plants to be absorbed by the plant root system since 95-99% of phosphate in nature is present in insoluble form. Soil samples from different irrigation systems from Akar-akar village were isolated through serial dilution techniques and grown on NA media shown that the higher the dilution, the fewer colonies that grew on the media. Macroscopic and microscopic observations were made to see the criteria for bacteria, shown that the bacteria in the three soil samples were gram negative and was known that bacillus and cocobacillus bacteria present in the three soil samples. Coccus bacteria was found in soil without irrigation and drip-surface irrigated soil, while streptococcus bacteria was found in drip-surface and drip-subsurface irrigated soil. As many as 22 bacterial isolates were isolated and grown on Pikovskaya media, only one bacterial colony was phosphate solvent through a clear zone that grew around the bacterial colony. The bacterial colony has a phosphate dissolving index (IPF) of 250, the ratio between colony diameter and clear zone diameter was 1: 1.5.Keywords – PGPR, Drip-surface irrigated soil, Drip-subsurface irrigated soil